Biofloc technology (BFT): Adjusting the levels of digestible protein and digestible energy in diets of Nile tilapia juveniles raised in brackish water - Durigon E.G.* (2020)
© 2019 Shanghai Ocean UniversitySeveral studies have been performed adjusting the levels of dietary digestible protein and digestible energy for tilapia, but none of them was performed in biofloc technology (BFT) system, especially in brackish (10) water. In this sense, three levels of digestible protein (22, 26 and 30% DP) and three levels of digestible energy (3000, 3150 and 3300 kcal DE / kg) were evaluated on growth performance, body composition, hematological parameters and planktonic community in juveniles of Nile tilapia (O. niloticus) raised under BFT conditions. A total of 540 tilapia fingerlings (GIFT strain with 1.25 ± 0.15 g initial weight) were reared during 42 days in thirty-six plastic tanks (75 L), fed three times a day. No interaction was detected in the parameters evaluated. The fish fed with feed containing 26% and 30% of DP obtained higher final weight, specific growth rate and condition factor as compared to those fed with 22% of DP (P < 0.05). Body protein on tilapia carcass increased proportionally according to dietary protein. The higher dietary energy level promoted a higher body lipid deposition. According to hematological parameters fish from all treatments presented a satisfactory immunological status. The monitoring of planktonic community indicated a variation over time, specially on the number of dinoflagellates, rotifers and microalgae. The results indicated that diets containing 26% of DP and 3150 kcal / kg of DE for Nile tilapia juveniles promoted suitable growth performance and health conditions when reared in biofloc brackish water, and enabled savings in regards to dietary protein once the energy levels were adjusted.